Market Reaction to Bond Rating Announcements: Evidence from Infrastructure Firms - Nafisah, Silmy Maulan; Fadli, Faishal (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Debt credibility signals through bond rating announcements are crucial information, especially for capital-intensive sectors such as infrastructure sector. This study examines the Indonesian infrastructure sector’s stock market reaction to bond rating announcements during 2023. Using an event study methodology with a 15-day event window on a sample of 14 companies, this research analyses actual and expected returns before and after the announcement event, as well as abnormal returns before, during, and after the announcement event. Abnormal returns are calculated as the difference between actual returns and expected returns that estimated using the market-adjusted model. The primary findings show no statistically significant abnormal returns before, during, or after the announcement date. Although data observations indicate a pattern of delayed market reactions, the effect is not strong enough to generate abnormal returns. This finding is consistent with the semi-strong form of the efficient market hypothesis, which implies that public information from bond rating announcements is anticipated and already fully reflected in stock prices.